Dietary intake pattern among breast cancer survivors in East Coast of Peninsular Malaysia - Sharifah Wajihah Wafa, Syed Saadun Tarek Wafa; Laila Ruwaida, Mohd Zainuddin; Lin, L.P; Aryati, Ahmad (2016)
Dietary intake plays a significant role in the prognosis of breast cancer and is one of the modifiable factors in preventing cancer recurrence. This study aims to describe the dietary intake pattern among breast cancer survivors in East Coast of Peninsular Malaysia. A total of 74 breast cancer survivors, aged 37 to 72 years, with mean duration of survivorship of 6. 1 + 4.4 years were recruited from two main referral hospitals in Terengganu and Kelantan. Majority of the respondents were Malay (93.2%) with a mean BMI of 27 .9 + 4.9 kg/mr, and were diagnosed with stage II cancer (37 .8o/o). Dietary intake was estimated using a validated interviewer administered semi-quantitative food frequency questionnaire, which included 203 food items. These food items were then grouped into several food groups for assessment of adherence towards the Malaysian Dietary Guidelines. The mean daily intake of energy was 2051 1897 kcal, protein was 81.9 r34.4 g(16% of energy), carbohydrate was 295.6 t l2g.g g(S7o/o of energy) and fatwas 60.5 !32.7 g(27oh of energy). overall, breast cancer survivors in this study had an adequate daily intake of vitamins and minerals according to RNI recommendations except for dietary fibre (12.5 t 7.3 g), calcium (640'7 +_ 367'4 g) and potassium (2112.4 r go2.1 mg). In comparison to Malaysian Dietary Guidelines respondents showed adequacy of meat, poultry, egg intake (1.0 serving/day), while higher intake of cereal and grains (10.6 serving/day), fruits (2.7 servings/day) and fish, shellfish and seafood (1 .8 servings/ day). Inadequate intake was reported for vegetables (1.7 servings/ day), legumes (0.1 serving/day), milk and dairy products (0.6 serving/day). In a nutshell, breast cancer survivors in East Coast of Peninsular Malaysia had an adequate intake of most macro-, micro-nutrients, and major food. group recommendations' Additional time spend to reinforce good nutrition by medical doctors during biannual follow-up consultation had improved intake and perhaps this could be followed by other hospitals.